2005
DOI: 10.1038/sj.eye.6701918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posterior capsular opacification removal on automated perimetry

Abstract: Purpose Although posterior capsular opacification (PCO) is a common phenomenon in a considerable number of ophthalmologic patients, no prospective controlled trials assessing its influence on automated perimetry exist. This technique continues as a standard in the diagnosis of glaucoma and neuroophthalmological diseases. The aim of the present report is to investigate the effect of PCO on automated visual field examination. Methods A total of 26 PCO affected eyes of 26 patients had Humphrey SITA standard (prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…Several researchers have reported that MD improved after cataract surgery [ 11 13 ]. Similarly according to our results, amelioration of MD occurred after capsulotomy [ 14 ].…”
Section: Effect Of Pco On Automated Perimetrysupporting
confidence: 86%
See 2 more Smart Citations
“…Several researchers have reported that MD improved after cataract surgery [ 11 13 ]. Similarly according to our results, amelioration of MD occurred after capsulotomy [ 14 ].…”
Section: Effect Of Pco On Automated Perimetrysupporting
confidence: 86%
“…The effect that cataract has on automated perimetry has been well investigated [ 11 13 ]. Our research group completed a study in eyes of patients with PCO who underwent a white-on-white automated perimetry test (Humphrey SITA standard programme 24-2) immediately before Nd:YAG capsulotomy and between postsurgery weeks 1 and 8 [ 14 ]. The compared pre- and postlaser perimetric indices were mean defect (MD) and pattern standard deviation (PSD).…”
Section: Effect Of Pco On Automated Perimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior capsule opacification (PCO) also causes light scatter, which reduces retinal contrast and results in reduced retinal threshold sensitivity. 50 Anterior axial movement of the IOL from capsular bag contraction is also a possible explanation for the decreasing incidence over time because it could reduce the axial space behind the iris to 0.06 mm or less. However, it would also be associated with a myopic shift in the patient's refraction, which is extremely rare with contemporary Figure 15.…”
Section: Natural Course and Treatmentsmentioning
confidence: 98%
“…Por otro lado evidenciamos también que algunos campos previos a la capsulotomía presentaban defectos que simulaban escotomas arqueados. Una vez realizado el láser, dichos artefactos desaparecieron (7). A efectos prácticos, por tanto, se podría confundir en determinados casos un defecto campimétrico producido por una OCP con un defecto campimétrico glaucomatoso (falso positivo).…”
unclassified